Contagion and the beginning of the crisis - Pre-Lehman period - Júlia Király; Márton Nagy; Viktor E. Szabó (Magyar Nemzeti Bank, 2008)
This paper provides an overview of the antecedents, main drivers and spillover mechanisms of the turbulence emanating from the US sub-prime credit market in the summer of 2007. Its primary goal is to discuss the facts and interrelationships featured in the various analyses and statistics in a uniform, non-standard approach, to separate the 'centre' from the 'periphery' in terms of the impact of contagion, and to understand the causes and consequences in the pre-Lehman period. The paper concludes that the primary causes of the turmoil were a persistently low international interest rate environment and financial imbalances engendered by globalisation. The combination of accelerating house price inflation and rapid financial asset price rises due to sub-prime mortgage credit securitisations (the originate-and-distribute model) as well as thebursting of asset price bubbles collectively were responsible for the magnitude of the distress. The spillover from the turmoil, in turn, was the consequence of increased international financial integration. One innovation of the paper is a detailed analysis of the channel of contagion within financial integration: a confidence crisis, coupled with turbulence in the interbank markets, played a major role in the centre, while on the periphery the triggers were internal vulnerability, rises in risk premia and reduced access to credit.
Keywords: G20; G30; 330; sub-prime; turmoil; turbulence; mortgage credit; Finanzkrise; Kreditmarkt; Hypothek; Verbriefung; Strukturiertes Produkt; Derivat; USA; Welt